The world book: student discovery encyclopedia Atlas/Index volume 13 - World Book, Inc (Chicago: World Book, 2005)
A general elementary encyclopedia with brief illustrated articles covering an alphabetical array of topics
Keywords: encyclopedia,Children's encyclopedias and dictionaries